Brexpiprazole-Associated Pisa Syndrome (Pleurothotonus) in a Patient With Dementia. Issue 3 (14th May 2022) - Nagai, Yasuhito; Yamazaki, Takahiro; Sugita, Tomoyuki; Shibata, Nobuto
Abstract : Objectives: The aims of the study were to report brexpiprazole-induced Pisa syndrome (PS) in a patient with Alzheimer disease and to discuss the pathophysiology and the treatment of PS. Methods: We report a 71-year-old female patient with Alzheimer disease. After 2 months medication of brexpiprazole, she presented PS. By switching to quetiapine, the symptom was ameliorated; however, transient acute dystonia was occurred. Conclusions: Drug-induced PS may be associated with dopamine-acetylcholine imbalance. This imbalance causes the dysfunction of the cortex and basal ganglia and the dysfunction of sensory and somatosensory system. Stopping the offending drugs is a choice for the treatment of PS. This is the first report of PS-induced brexpiprazole.